Advanced power generation systems - Dincer, Ibrahim, 1964- (Elsevier Science, 2014)
Advanced Power Generation Systems examines the full range of advanced multiple output thermodynamic cycles that can enable more sustainable and efficient power production from traditional methods, as well as driving the significant gains available from renewable sources. These advanced cycles can harness the by-products of one power generation effort, such as electricity production, to simultaneously create additional energy outputs, such as heat or refrigeration. Gas turbine-based, and industrial waste heat recovery-based combined, cogeneration, and trigeneration cycles are considered.